Pola Pengobatan Insulin dan Ace - Inhibitor pada Pasien Diabetes Melitus Tipe 2 dengan Hipertensi Terhadap Kontrol Glikemik dan Tekanan Darah - chitra astari (Universitas Mataram, 2020)
This research aimed to analyze the insulin and ACE Inhibitor therapy to patients with DM type 2 with hypertension, and giving a picture about the influence on the blood sugar control and blood pressure using the parameter of fasting blood glucose, HbA1C, and blood pressure. The research was conducted in the endocrine clinic of DR. Wahidin Sudirohusodo General Hospital, Makassar, from 2 May through 12 July, 2016. The research was a Cross-Sectional study with the samples chosen using the evhaustive sampling technique. The types of insulin and antihypertension class ACE inhibitor as revealed by the interviews with the patients. The therapy effects of pre and post interventions were analyzed using the parameter of glycemia, and HbA1C using the pair sample T-test and blood pressure using Wilcoxon test. The research results indicated that the level of blood sugar after fasting was reduced to 64.08 and the level of HbA1C was reduced to 1.51 with the value of P = 0.000. The parameter of systolic and diastolic blood pressures had equal degradation of 12.56 and 12.32 respectively with value of P = 0.000, meaning P<0.05 in statistics.